Coarse‐Grained and Atomistic MD Simulations of RNA and DNA Folding. Issue 8 (13th May 2014) - Leuchter, Jessica D.; Green, Adam T.; Gilyard, Julian; Rambarat, Cecilia G.; Cho, Samuel S.
Abstract Although the main features of the protein folding problem are coming into clearer focus, the microscopic viewpoint of nucleic acid folding mechanisms is only just beginning to be addressed. Experiments, theory, and simulations are pointing to complex thermodynamic and kinetic mechanisms. As is the case for proteins, molecular dynamics (MD) simulations continue to be indispensable tools for providing a molecular basis for nucleic acid folding mechanisms. In this review, we provide an overview of biomolecular folding mechanisms focusing on nucleic acids. We outline the important interactions that are likely to be the main determinants of nucleic acid folding energy landscapes. We discuss recent MD simulation studies of empirical force field and Go‐type MD simulations of RNA and DNA folding mechanisms to outline recent successes and the theoretical and computational challenges that lie ahead.